Patterns and outcome of relapse after autologous stem cell transplantation for mantle cell lymphoma - Dietrich, Sascha; Tielesch, Blanca; Rieger, Michael; Nickelsen, Maike; Pott, Christiane; Witzens-Harig, Mathias; Kneba, Michael; Schmitz, Norbert; Ho, Anthony Dick; Dreger, Peter (Cancer, 2011)
BACKGROUND: Autologous stem cell transplantation (autoSCT) has improved the outcome of patients with mantle cell lymphoma (MCL) considerably. However, little is known about the patterns and outcome of MCL recurrence after autoSCT. METHODS: The authors conducted a retrospective study of 118 patients with MCL who underwent autoSCT from August 1992 to August 2008 at 3 different referral centers in Germany. RESULTS: Fifty-two relapses occurred for a cumulative incidence of 46% after 5 years. Only 3 patients relapsed after 5 years (at 90 months, 91 months, and 171 months) after undergoing autoSCT. A Cox regression analysis of the incidence of relapse identified not receiving rituximab before autoSCT and undergoing salvage autoSCT as predictive factors for relapse, whereas cytosine arabinoside intensification; a total body irradiation-based, high-dose regimen; patient age; and year of transplantation had no influence. The median overall survival (OS) after relapse was 23 months. Twenty patients (39%) underwent allogeneic stem cell transplantation (alloSCT) for relapse, and 11 of those patients remained in ongoing complete remission at the time of the current report. It is noteworthy that there were 4 long-term survivors who lived for >5 years after relapse even without undergoing alloSCT. A Cox regression analysis of OS after relapse revealed that the response duration after autoSCT was an adverse predictor of OS, whereas alloSCT was associated with a significantly longer OS after relapse. CONCLUSIONS: The current results indicated that autoSCT was capable of inducing long-term remission up to 16 years after treatment, but the outcome of patients with MCL who relapsed after autoSCT was poor, especially if their response duration after autoSCT was short. However, for a subset of patients with relapsed MCL, alloSCT may offer the possibility of durable survival, and individual patients can enjoy long-term survival after relapse even without undergoing alloSCT. Cancer 2011. © 2010 American Cancer Society.